LITERASI DIGITAL BERETIKA UNTUK GENERASI Z: PENGABDIAN MASYARAKAT DALAM SEMINAR DARING TENTANG BISNIS BERKELANJUTAN - Astuti, Andarweni; Saputra, Deri (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Generation Z faces challenges in conducting ethical digital businesses amidst rapid technological advancements. Many of them are tempted to gain instant profits without considering moral and security aspects. The online seminar